Neocortical and cerebellar malformations affect flurothyl-induced seizures in female C57BL/6J mice - Keever, Katherine M.; Li, Ying; Womble, Paige D.; Sullens, D. Gregory; Otazu, Gonzalo H.; Lugo, Joaquin N.; Ramos, Raddy L. (Frontiers in Neuroscience, 2023)
Brain malformations cause cognitive disability and seizures in both human and animal models. Highly laminated structures such as the neocortex and cerebellum are vulnerable to malformation, affecting lamination and neuronal connectivity as well as causing heterotopia. The objective of the present study was to determine if sporadic neocortical and/or cerebellar malformations in C57BL/6J mice are correlated with reduced seizure threshold. The inhaled chemi-convulsant flurothyl was used to induce generalized, tonic-clonic seizures in male and female C57BL/6J mice, and the time to seizure onset was recorded as a functional correlate of brain excitability changes. Following seizures, mice were euthanized, and brains were extracted for histology. Cryosections of the neocortex and cerebellar vermis were stained and examined for the presence of molecular layer heterotopia as previously described in C57BL/6J mice. Over 60% of mice had neocortical and/or cerebellar heterotopia. No sex differences were observed in the prevalence of malformations. Significantly reduced seizure onset time was observed dependent on sex and the type of malformation present. These results raise important questions regarding the presence of malformations in C57BL/6J mice used in the study of brain development, epilepsy, and many other diseases of the nervous system.